Cyanolichen research: a bibliometric analysis from 1991 to 2022 (Research, Society and Development, 2022)
In the present study, a bibliometric analysis was carried out on cyanolichens, using the ISI Web of Science (WoS) as a database. A total of 244 documents were retrieved, published in the period from 1991 to 2022, and 79 studies published from 2016 to 2022. Considering the entire period analyzed, there was an increase in studies with cyanolichens, with 2013 being the most productive year (21 studies), followed by 2019 (18). The studies were carried out by scientists from 47 countries, with the US, Canada, Germany, Norway and Sweden as the most productive. The bibliometric network of keywords was grouped into four classes: the first and most isolated included taxonomy, evolution and selectivity of symbiotic partners, while the other three classes were associated with ecology, physiology, diversity and conservation of cyanolichens, the latter arranged in a closer relationship, showing that these aspects are often studied together. Analyzing only the period from 2016 to 2022, most of the studies cited show a growing interest in studying nitrogen fixation, functional ecology, associated microbiota and macroevolution of cyanolichens. The bibliometric analysis was effective in demonstrating the state of the art of the study of cyanolichens in a global context, and highlighted the main topics of interest to the scientific community, as well as the countries, researchers, studies and journals that stood out.